ISLAMIC PERSPECTIVE OF HUMAN BEING CHARACTERISTICS IN WILLIAM BLAKE’S POEMS - Mulyo, Wahyu Tejo; Afifuddin, Muzakki; Purbani, Widyastuti (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This paper attempts to discover the characteristics of the human being through William Blake's Poems as an alternative definition. Among Blake's poems, The Divine Image and The Human Abstract are the most representative of discovering human characteristics. Moreover, this study strives to establish the correlation between Islamic values and European literature. The study uses new criticism in discovering the characteristics in the poems by two steps of analysis; paraphrasing and explication. After conducting the analysis, it is found that there are four positive characteristics in The Divine Image and four negative characteristics in The Human Abstract. The positive characteristics consist of mercy, pity, peace, and love, while the negative ones are exploitation, cruelty, conflict, and hypocritical humility. An Islamic expert, Murtadha Muthahhari, perceives the result of the analysis of the poem. Muthahhari explains fourteen positive and eight negative points of humans following the Holy Qur'an. It is found that the poems' human positive and negative characteristics include in MurtadhaMuthahhari's points of thought. Thus, the ideas of human being’s characteristics in the poems are related to Murtadha Muthahhari’s thoughts.